Necessary and Sufficient Conditions of Oscillation in First Order Neutral Delay Differential Equations - Songbai Guo; Youjian Shen; Binbin Shi (Abstract and Applied Analysis)
We are concerned with oscillation of the first order neutral delay differential equation [x(t)−px(t−τ)]′+qx(t−σ)=0 with constant coefficients, and we obtain some necessary and sufficient conditions of oscillation for all the solutions in respective cases 0<p<1 and p>1.